2015
DOI: 10.1038/jid.2014.525
|View full text |Cite
|
Sign up to set email alerts
|

Dermal CD14 + Dendritic Cell and Macrophage Infection by Dengue Virus Is Stimulated by Interleukin-4

Abstract: Dengue virus (DENV) is responsible for the most prevalent arthropod-borne viral infection in humans. Events decisive for disease development occur in the skin after virus inoculation by the mosquito. Yet, the role of human dermis-resident immune cells in dengue infection and disease remains elusive. Here we investigated how dermal dendritic cells (dDCs) and macrophages (dMs) react to DENV and impact on immunopathology. We show that both CD1c(+) and CD14(+) dDC subsets were infected, but viral load greatly incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 47 publications
1
45
0
1
Order By: Relevance
“…CD206 was highly expressed with significance in active BD patients with cutaneous symptoms (49.7 ± 35.2%) compared to inactive BD patients (4.7 ± 3.1%) ( p = 0.007) and HCs (7.4 ± 0.8%) ( p = 0.02). It is known that CD206 facilitates viral infections such as Dengue virus [28], hepatitis B virus [29], lymphadenopathy associated virus [30], and human immunodeficiency virus [31]. In collagen induced arthritis, CD206 was seen in the inflamed joints by micro-computed tomography imaging [32].…”
Section: Discussionmentioning
confidence: 99%
“…CD206 was highly expressed with significance in active BD patients with cutaneous symptoms (49.7 ± 35.2%) compared to inactive BD patients (4.7 ± 3.1%) ( p = 0.007) and HCs (7.4 ± 0.8%) ( p = 0.02). It is known that CD206 facilitates viral infections such as Dengue virus [28], hepatitis B virus [29], lymphadenopathy associated virus [30], and human immunodeficiency virus [31]. In collagen induced arthritis, CD206 was seen in the inflamed joints by micro-computed tomography imaging [32].…”
Section: Discussionmentioning
confidence: 99%
“…DENV infection on DCs resident in human dermis was also evaluated. Schaeffer and colleagues showed that the CD1c + and CD14 + dermal DC subsets, as well as dermal macrophages, are the primary cell targets for DENV, but the viral load increased in the CD14 + dermal DCs after stimulation with IL-4 (Schaeffer et al, 2015).…”
Section: Dendritic Cell Interactions With Dengue Virusmentioning
confidence: 96%
“…Interestingly CD141 + DCs, which make up a minority population in the skin, were not observed to be infected [21]. Macrophages and CD1c + and CD14 + dermal DCs that are matured with IL-4 have also been shown to be more susceptible to DENV infection, potentially due to the upregulation of DENV receptors, DC-specific ICAM3-grabbing non-integrin (DC-SIGN) and the mannose receptor, in response to the cytokine treatment [22]. In spite of being infection targets, monocyte/macrophage lineage cells could play a dual role in infection since it has been shown that depletion of macrophages leads to early reduced infection in lymph nodes, yet to later increased infection burden in vivo systemically [23].…”
Section: Infection Target Cell Types In the Skin And Virus Entry Recementioning
confidence: 99%